2016
DOI: 10.1039/c6ra00338a
|View full text |Cite
|
Sign up to set email alerts
|

Application of group V polyoxometalate as an efficient base catalyst: a case study of decaniobate clusters

Abstract: We demonstrated for the first time that [Nb10O28]6− exhibited base catalytic activity for aldol-type condensation reactions including Knoevenagel and Claisen–Schmidt condensation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…The solution-state 17 O NMR spectra of [V10O28] 6− (enriched by the addition of H2 17 O) show an up-field shift of the 17 O NMR signals assignable to OB and OC upon acidification with HCl [71,74]. It has been reported that the protonation of oxygen atoms in POMs [38,55,56]. …”
Section: Isopolyoxometalatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The solution-state 17 O NMR spectra of [V10O28] 6− (enriched by the addition of H2 17 O) show an up-field shift of the 17 O NMR signals assignable to OB and OC upon acidification with HCl [71,74]. It has been reported that the protonation of oxygen atoms in POMs [38,55,56]. …”
Section: Isopolyoxometalatesmentioning
confidence: 99%
“…This bifunctionality facilitates the nucleophilic attack of the NH2 and OH groups on the carbon atom of CO2 to form the corresponding carbamic and carbonic acids followed by transformation to the final products. On the other hand, Cummins and co-workers reported that the reaction of After the report on the chemical fixation of CO2 with TBA2[WO4], various catalytic systems based on tungstates and niobates have been developed [48,[53][54][55][56][57]. The Ag2[WO4] catalyst system in combination with the Ph3P ligand could efficiently catalyze CO2 fixation such as carboxylative cyclization of propargyl alcohols and one-pot synthesis of oxazolidinones and carbamates (Schemes 4 and 5) [48,54].…”
Section: Chemical Fixation Of Co2mentioning
confidence: 99%
“…Density functional theory calculations, particularly natural bond orbital (NBO) analysis, were applied in order to obtain localized charge on the oxygen atoms. It was proved that NBO charge of O b (−0.873) in [Nb 10 O 28 ] 6− was the lowest through the composing oxygen atoms and thus the tetraalkylammonium salts of decaniobate cluster could successfully serve as catalysts in the Knoevenagel condensation and CO 2 fixation to epoxides (Hayashi et al, 2016 , 2017 ).…”
Section: Catalysis On Polyoxoniobatesmentioning
confidence: 99%
“…We previously demonstrated that adecaniobate cluster([Nb 10 O 28 ] 6À )showedBrønsted base catalysis for Knoevenagel condensation reaction and, based on density functional theory (DFT) calculation, we proposed that the surfaceOatoms providet he base sites. [15] Group VP OMs bearing surface Oa toms with al arge negative chargea re potential candidates for Lewis base catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…This led us to a simple working hypothesis that group V POMs, which has been applied to catalytic decomposition of toxic nerve agents, act as a strong base catalyst because of a large negative charge. We previously demonstrated that a decaniobate cluster ([Nb 10 O 28 ] 6− ) showed Brønsted base catalysis for Knoevenagel condensation reaction and, based on density functional theory (DFT) calculation, we proposed that the surface O atoms provide the base sites . Group V POMs bearing surface O atoms with a large negative charge are potential candidates for Lewis base catalysts.…”
Section: Introductionmentioning
confidence: 99%